Rethinking Team Viability: Literature Review and New Conceptualisation - Kukyte, Aiste; Jasinskas, Edmundas; Tamasevicius, Virginijus (Transformations In Business & Economics, 2026)
This study focuses on the concept of team viability. Following a literature review on team viability, this study first analyses the historical confusion and inconsistency in how team viability has been defined and measured, as well as compared to similar constructions such as team satisfaction, cohesion, or willingness to stay in the team. The literature synthesis helped categorise the various conditions essential for team viability into six distinct groups: organisational context, team composition, leadership style, team synergy, and teamwork results, which were drawn from both theoretical and recent empirical research. Finally, a new, more precise definition of team viability is formulated to guide future research and the development of a more reliable team viability assessment instrument.